Research on the Electric Field Distribution and Structure Optimizing  of Integral Prefabricated Joint and Taped Joint - CHEN Zhen-xin; YU En-ke; WANG Yang; ZHOU Ze-wei; DUAN Ran; QUE Shan-ting; LE Yan-jie; CHEN Guo-zhi (Journal of Harbin University of Science and Technology)
Integral prefabricated joint and taped joint are two kinds of widely used cable joint.Because of the different structure and conductivity of insulation, there is great difference in the electric field distribution between the two kinds of joints .In this paper, 50.kV crosslinked polyethylene high voltage dc cable joint is selected as the research object, models of Integral Prefabricated Joint (silicone rubber insulated) and taped joint (oil impregnated paper insulated) was established and the electric field distribution in the joints was analyzed by comsol software.It is found that the electric field at the root of stress cone reached 45.kV/mm for Integral Prefabricated Joint‎The electric field at the root of stress cone was nearly 0.kV/mm for taped joint but the electric field at the top of reversed stress cone reached 30.kV/mm.By optimizing the structure of the taped joint, the maximum electric field is reduced to 7.kV/mm.By using Teflon as the taped insulation which can reduce the maximum electric field to 3.kV/mm.The research is a reference in the HVDC cable joints design